The Age Of Gamers And Their Representation Of Sexual Orientation And Gender Identity Through Avatars (Journal of Namibian Studies : History Politics Culture, 2023)
The video game industry now holds a significant share of the global market, and the consumption of video games has given rise to avatars and online societies. Video games impact the real world by enabling individuals to represent themselves through avatars in virtual spaces, driven by various motivations. Many scholars are interested in studying the variables related to the identity and gender of gamers to find correlations with their representation in the game. However, many researchers in these studies primarily focus on biological sex and do not thoroughly explore sexual orientation and gender identity (SOGI) in relation to gamers and their avatars. This research inquiry aims to investigate the gaming population's biological sex, gender identity, sexual orientation, and age to discern patterns in how they express gender through their avatars.Data were collected through online questionnaires using Google Forms in online social media gaming communities, primarily Facebook. The study focused on popular games from three distinct genres: action (Grand Theft Auto), MMORPG (Black Desert Online), and simulation (The Sims 4), where players can freely customize their avatars. The sample group consists of 420 individuals. Among them, 52.6% were identified as male, and 47.4% (identified as) female. The average age of the gamer sample was 22.75 (SD = 6.17). Age and Sex Ratios (ASRs) indicate a trend among this younger generation towards not adhering strictly to the gender binary. In terms of sexual orientation, most gamers identified themselves as heterosexual, but in terms of gender identity, many identified themselves as queer.